Fractional order SMC for speed control of PMSM - Zaihidee, F.M.; Mekhilef, Saad; Mubin, Marizan (2018)
A fractional order sliding mode control with PIDsliding surface design (FOSMC-PID) is proposed in this research. This controller incorporates fractional calculus which has a slower energy transfer compared to integer order calculus in order to suppress the chattering. Stability of this controller is analyzed using Lyapunov stability theorem. Simulation results proved that the proposed FOSMC speed controller performs as a robust and fasf anti-disturbance controller to regulate the speed of a PMSM and proven its advantages against SMC controllers. The proposed sliding surface design also improves the FOSMC in terms of torque ripple reduction, chattering reduction and anti-disturbance properties, compared to FOSMC with PI or PD sliding surface.